Improving Data Embedding Capacity in LSB Steganography Utilizing LSB2 and Zlib Compression - Kurniawan, Joshua Calvin; Nugraha, Adhitya; Prayogo , Ariel Immanuel; Novanto , The, Fandy (Politeknik Ganesha Medan, 2024)
In an increasingly advanced era, the exchange of information through digital tools has become a common practice. With easy access and advancing facilities, securely and covertly exchanging data has become a challenging task. Therefore, the technique of steganography can be used as a solution for data hiding and protection, enabling safer data exchanges. Steganography is a method to conceal data within a transmission object, which can be an image, video, audio, and more. In this research, steganography will be performed using images as the transmission object. This study is done to offer a modification of the Least Significant Bit (LSB) steganography technique by utilizing the LSB-2 method, along with the utilization of the Zlib compression algorithm. The modification and use of the Zlib compression algorithm aim to increase the message capacity that can be embedded in the transmission object while preserving the image quality. The results of the experiments will be presented in tabular form by comparing the original image with the steganography-processed image using metrics such as Mean Square Error (MSE), Peak Signal-to-Noise Ratio (PSNR), and Structural Similarity Index (SSIM) as measures of image quality. The experiments conducted results in an increase of capacity of approximately 36.54%, an increase in PSNR value of approximately 4.72%, accompanied by a decrease in MSE value in average of 49.19%, and SSIM values constantly at 0,99999 thus proving the proposed method successfully increased the embedded massage capacity while preserving even enhance the quality of the stego image produced by the embedding process